(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Inulin is a natural polysaccharide produced from organisms and microorganism. Inulin is a type of fructan that ?-amylase cannot digest it and cannot hydrolysis by hydrolytic enzymes. It was used to get non-fat fermented milk and it’s a type of prebiotics that induce growth and activity of probiotics bacteria, thus improving the health. Pseudomonas fluorescens have the capacity to produce inulin when grown in media supplied with sucrose. Twenty-two of bacterial isolates were belong to Pseudomonas fluorescens depending on structural features, microscopic checking, biochemical analysis and flourescent pigments that produced on King B medium. Ten isolates of P. fluorescens had strongly degree of mucous growth on solid production medium, the gummy and mucous manifestation on agar medium containing sucrose were give rise to inulin production. Inulin produced from P. fluorescens was analyzed by Fourier Transform Infrared Spectroscopy to detect functional groups which it was (C-O, CH, OH and C=O) and by Thin Layer Chromatography to determine its components of monosaccharide. Inulin distinguished as dark spot on white background and the Rf of it was (0.58). The best product of inulin were in production salt agar medium containing 20% sucrose, pH =7, Temperature =370C without nitrogen sources and the inoculum size 1%, it was (3.2 gm ?100 ml). The effects of bacterial inulin on the growth of Saccharomyces cerevisiae was studied by culturing it in medium supplemented with 3% of bacterial inulin at 30°C for 48 hrs. The results showed there was no remarkable effect of inulin on Saccharomyces cerevisiae growth in comparison to control.